Assessing Post-Treatment Pathologic Tumor Response in Female Genital Tract Carcinomas: An Update - Inzani, Frediano; Arciuolo, Damiano; Angelico, Giuseppe; Santoro, Angela; Travaglino, Antonio; D’Alessandris, Nicoletta; Scaglione, Giulia; Valente, Michele; Cianfrini, Federica; Raffone, Antonio; Zannoni, Gian Franco (Frontiers in Oncology, 2022)
In the last decades, several new therapeutic strategies have been introduced in the field of gynecologic oncology. These include neoadjuvant chemotherapy for high-grade serous tubo-ovarian carcinoma, hormonal fertility-sparing strategies for endometrial cancer, pressurized intraperitoneal aerosol chemotherapy (PIPAC) for surgically incurable peritoneal metastasis, and neoadjuvant treatments for locally advanced cervical carcinomas. All these recent advances lead to the development of novel scoring systems for the evaluation of pathological response related to specific treatments. In this regard, pathological evaluation of the morphological modifications related to these treatments and the definition of a tumor regression grading score have been introduced in clinical practice in order to achieve a more efficient prognostic stratification of patients affected by gynecological malignancies. The aim of the present paper is to provide a detailed review on the post-treatment pathological scoring systems in patients affected by gynecological malignancies.